Resolvin E1, an endogenous lipid mediator derived from eicosapentaenoic acid, prevents dextran sulfate sodium–induced colitis - Ishida, Tsukasa; Yoshida, Masaru; Arita, Makoto; Nishitani, Yosuke; Nishiumi, Shin; Masuda, Atsuhiro; Mizuno, Shigeto; Takagawa, Tetsuya; Morita, Yoshinori; Kutsumi, Hiromu; Inokuchi, Hideto; Serhan, Charles N.; et al. (Inflammatory bowel diseases, 2010)
Resolvin E1 (RvE1), an endogenous lipid mediator derived from eicosapentaenoic acid, has been identified in local inflammation during the healing stage. RvE1 reduces inflammation in several types of animal models including peritonitis and retinopathy and blocks human neutrophil transendothelial cell migration. The RvE1 receptor ChemR23 is expressed on myeloid cells such as macrophages and dendritic cells. The aim of this study was to determine whether RvE1 regulates colonic inflammation when the innate immune response of macrophages plays a key role in pathogenesis and tissue damage.MethodsThe RvE1 receptor ChemR23 was expressed in mouse peritoneal macrophages as defined by flow cytometry. Peritoneal macrophages were pretreated with RvE1, followed by lipopolysaccharide stimulation, whereupon transcriptional levels of proinflammatory cytokines were analyzed.ResultsRvE1 treatment led to inhibition of proinflammatory cytokines including TNF-α and IL-12p40. In HEK293 cells, pretreatment with RvE1 inhibited TNF-α-induced nuclear translocation of NF-κB in a ChemR23-dependent manner. These results suggested that RvE1 could regulate proinflammatory responses of macrophages expressing ChemR23. Therefore, we investigated the beneficial effects of RvE1 in dextran sulfate sodium–induced colitis. RvE1 treatment led to amelioration of colonic inflammation.ConclusionsThese results indicate that RvE1 suppresses proinflammatory responses of macrophages. RvE1 and its receptor may therefore be useful as therapeutic targets in the treatment of human inflammatory bowel disease and other inflammatory disorders. Inflamm Bowel Dis 2010